2011
DOI: 10.1590/s1517-86922011000400002
|View full text |Cite
|
Sign up to set email alerts
|

Atividade física e sintomas do envelhecimento masculino em uma população do sul do Brasil

Abstract: The aim of this study was to verify the association of aging male symptoms with physical activity in leisure and commuting time in men aged 40 years or older from Pelotas, a city in Southern Brazil. Methods: a population-based cross-sectional study was carried out including 421 men, living in the urban area. To verify the aging male symptoms, the Aging Males' Symptoms Scale (AMS) was used and to evaluate physical activity level, the International Physical Activity Questionnaire (IPAQ), long version was used. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
12

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
(39 reference statements)
0
2
0
12
Order By: Relevance
“…The practice of physical activities favors social interaction, improves self-assuredness (belief of the individual in his/her capacity to perform specific tasks) and provides higher sensation of control over the events and demands of the environment. Moreover, increase in the physical activity level is related to improvement in the depression and anxiety symptoms, better tolerance to stress and increase in self-esteem 19,20 , reducing isolation and favoring socialization of new groups 21 . In a study with elderly from Florianópolis 22 , SC, findings different from the ones found in the present study were observed, since most part of the elderly was considered non-sedentary (59.3%), being the domain leisure the one which contributed the most to the active condition of the male sex and the domain domestic activities to the female sex; another study carried out in the city of Pelotas 20 with male individuals from 40 years old corroborates the data of this research, with 82.9% of the individuals being classified as insufficiently active in leisure.…”
Section: Discussionmentioning
confidence: 99%
“…The practice of physical activities favors social interaction, improves self-assuredness (belief of the individual in his/her capacity to perform specific tasks) and provides higher sensation of control over the events and demands of the environment. Moreover, increase in the physical activity level is related to improvement in the depression and anxiety symptoms, better tolerance to stress and increase in self-esteem 19,20 , reducing isolation and favoring socialization of new groups 21 . In a study with elderly from Florianópolis 22 , SC, findings different from the ones found in the present study were observed, since most part of the elderly was considered non-sedentary (59.3%), being the domain leisure the one which contributed the most to the active condition of the male sex and the domain domestic activities to the female sex; another study carried out in the city of Pelotas 20 with male individuals from 40 years old corroborates the data of this research, with 82.9% of the individuals being classified as insufficiently active in leisure.…”
Section: Discussionmentioning
confidence: 99%
“…A percepção na associação dos sintomas do envelhecimento com o nível de atividade física mostra que os sintomas psicológicos e somáticos diferenciam significativamente entre os idosos sedentários e os ativos em Pelotas no Rio Grande do Sul. Demonstrou-se que 90% dos sedentários apresentavam sintomas graves (10) . Quando comparados com esses dados, o estudo realizado com os idosos do PAI mostra uma relação de satisfação e realização quando destacamos o domínio Vitalidade para aqueles que também praticam atividade física.…”
Section: Resultsunclassified
“…Algumas alterações do envelhecimento se mostram mais evidentes em idosos inativos, quando comparados os relatos dos sujeitos da mesma idade que realizam alguma atividade física. Vale ressaltar que o envelhecimento é um processo multifatorial, e envelhecer está ligado à capacidade de adaptação do individuo às exigências do meio ambiente no qual está inserido, e que a realização de atividade física ajuda o corpo a reagir ou adaptar-se a fatores de dificuldades na realização de suas atividades diárias (10)(11) . Nessa perspectiva, o envelhecimento ativo é apontado como uma forma de suavizar, ou amenizar os efeitos correlacionados ao avanço da idade, envelhecer ativo permite às pessoas realizar seus potenciais de bem estar para atividade social e mental durante o curso da vida envolvendo-se com a sociedade.…”
Section: Introductionunclassified
“…É possível que a mesma influencie na menor prevalência dos sintomas, haja vista que a sintomatologia geral do envelhecimento masculino é decorrente destes aspectos 8 . Assim, menores nível de AF pode contribuir para maior ocorrência da sintomatologia.…”
Section: Discussionunclassified
“…Os estudos com homens nesta faixa etária, se concentram em países da América do Norte, Europa e Oceania 6,7 . Considerando ser uma população que se prepara para o processo do envelhecimento, e pode enfrentar sintomas somáticos, psicológicos e sexuais, caracterizando os sintomas do envelhecimento masculino, é imperativo o estudo da AF, como forma de auxiliar a experenciar este processo natural de forma menos danosa, à saúde 8 . Além disso, identificar os fatores que se associam à AF em homens, pode ser um determinante ao incentivo de sua prática em diferentes intensidades, faixas etárias e condições de saúde.…”
Section: Introductionunclassified